DESIGN OF A WEBSITE-BASED KITCHEN INVENTORY SHOPPING SYSTEM (CASE STUDY: PARADISE DYNASTY) - Gulo, Yaferman; Putra, Eka; Hafni (Cattleya Darmaya Fortuna, 2024)
Paradise Dynasty faces challenges in managing kitchen inventory and shopping needs in an efficient and organized manner. The manual system implemented so far often causes recording errors, material shortages, or waste due to the lack of effective monitoring. Therefore, this research aims to design and develop a website-based kitchen inventory system to optimize the management of raw material stocks and shopping processes. The system is designed using a web-based technology approach that allows users to monitor stock availability, record shopping needs, and generate reports automatically. The development process is carried out through the stages of needs analysis, system design, implementation, and functionality testing. The system is also equipped with notification features for materials that are approaching the minimum stock limit, as well as shopping history to support management decisions. The results of the testing show that the system is able to improve efficiency and accuracy in kitchen inventory management. The system also helps reduce the risk of shortages or overstocks, and simplifies the operational decision-making process. Thus, the designed system is expected to be an innovative solution for Paradise Dynasty in supporting a more modern and integrated inventory management.